2020
DOI: 10.1186/s11671-020-03406-w
|View full text |Cite
|
Sign up to set email alerts
|

Stable High-Efficiency Two-Dimensional Perovskite Solar Cells Via Bromine Incorporation

Abstract: Two-dimensional (2D) organic-inorganic perovskites as one of the most important photovoltaic material used in solar cells have attracted remarkable attention. These 2D perovskites exhibit superior environmental stability and wide tunability of their optoelectronic properties. However, their photovoltaic performance is far behind those of traditional three-dimensional (3D) perovskites. In this work, we demonstrate the power conversion efficiency (PCE) of 2D perovskite solar cells (PVSCs) is greatly improved fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The grazing incidence X-ray diffraction (GIXRD) showed a peak below 10°, which is commonly attributed to the formation of a 2D perovskite layer. [51][52][53] The observed peak at 5.10° for TTMAI-treated 3D perovskite (Figure 1d) was initially assigned to TTMA 2 PbI 4 2D perovskite (n = 1). To support our claim, 2D perovskite (n = 1) was formed by coating TTMAI and PbI 2 (2:1) on SnO 2 , and GIXRD analysis was performed, which revealed a peak at 5.60° (Figure 1d).…”
Section: Resultsmentioning
confidence: 98%
“…The grazing incidence X-ray diffraction (GIXRD) showed a peak below 10°, which is commonly attributed to the formation of a 2D perovskite layer. [51][52][53] The observed peak at 5.10° for TTMAI-treated 3D perovskite (Figure 1d) was initially assigned to TTMA 2 PbI 4 2D perovskite (n = 1). To support our claim, 2D perovskite (n = 1) was formed by coating TTMAI and PbI 2 (2:1) on SnO 2 , and GIXRD analysis was performed, which revealed a peak at 5.60° (Figure 1d).…”
Section: Resultsmentioning
confidence: 98%
“…Minimal variation of effective thickness with time for MA 0.7 FA 0.3 PbI 3 deposited on glass is observed compared to that observed for MAPbI 3 on glass ( Table 1 ) within a similar time interval. The improved stability of mixed MA + FA perovskite can be attributed to the larger size of the FA cation compared to MA leading to a more favorable tolerance factor [ 14 , 53 ]. The ionic radii of MA and FA are 2.16 and 2.53 Å [ 54 ], respectively, and a larger FA cation fraction in the perovskite results in a more ideal Goldschmidt tolerance factor closer to 1 [ 14 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The improved stability for (FAPbI 3 ) 0.95 (MAPbBr 3 ) 0.05 over MAPbI 3 and MA 0.7 FA 0.3 PbI 3 with temperature variations and humidity exposure is attributed to the incorporation of Br into the mixed MA + FA film. Previous research has shown that including a small amount of Br enhances the stability, suppresses ion migration, and reduces trap-state density [ 53 ]. According to Noh et al, upon incorporation of Br into MAPbI 3 for solar cell absorbers, there is an improvement in open circuit voltage (V OC ) from 0.87 to 1.13 V and an increase in fill factor (FF) from 0.66 to 0.74 [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to bypass this obstacle, several researchers have turned to the familiar remedy employed in 3D perovskites: 226 the mixing of cations in the A-site in order to tune the tolerance factor. 227 Although this approach paid some dividends in terms of improved devices when the mixed compositions were employed to cast thin films, 107,128,228 the complete lack of structural characterization leaves the exact composition of the films in question. Nevertheless, in a few cases structural characterization has been achieved, showing that incorporation of FA is possible, as in the n = 4 DJ perovskite (3AMP)-(MA) 2.25 (FA) 0.75 Pb 4 I 13 (unpublished results in our laboratory).…”
Section: Directing Effects Of Spacersmentioning
confidence: 99%